EMPLOYEES' decision-making power in universities: Employees' right or taken for granted REALITIES? - Iman Tohidian; Abbas Abbaspour (Cogent Business & Management, 2020)
Internationally, state and non-state organizations are often managed based on an organization chart where sections are illustrated based on their management and decision-making power. Employees, as the main administrative body at these organizations, are generally represented as executive work forces-required to do whatever is assigned to them by senior management. Previous studies have investigated employees' job satisfaction within different contexts and from divergent perspectives. However, little attention has been paid to exploring employees' thinking power and their decision-making role within the organizations. This study explored the perspectives of 73 (46 male/27 female) university employees. The anonymized interviewees' responses were submitted to three top-level managers for their consideration. This paper presents the employees' feedback and managers' suggestions and proposes a series of recommendations around effective decision-making. The paper argues that it is important to engage top-tier management with the views of employees to improve relationships and productivity within organizations.
Keywords: 650; employees’ thinking power; managers’ priorities; university and policies; employees’ reflection; top-down level of organization charts